Management of powdery mildew of rapeseed-mustard - SUNITA SINGH,* R.B. SINGH, K.N. MAURYA; M.P. CHAUHAN, H.K. SINGH*, KETAN KUMAR, PRADIP KUMAR (Indian Phytopathology, 2016)
Out of 200 genotypes screened, 20 genotypes, namely, EC-414309, PBC-9221, NPC-14, BAUSM-92-1-1, PBC-2004-1, EC-339000, EC-338997, GSL-1, HNS-004, ONK-1, NRCDR-515, PBC-2002-2, NPC-15, OCN-3, EC-399299, NUDB-26-11, CAN-133, NPN-1, RGN-55, NRCR-837 showed consistently resistant reaction in both the years, while nine genotypes viz., EC-399296, EC-399301, EC-399313, PHR-2 , CAN-130, RAURD-101, RH-9301, SKM-9328, IJWHJ-001 were moderately resistant. Besides these, 30 genotypes exhibited moderately susceptible, 71 susceptible and 70 highly susceptible reactions. Three sprays of aqueous suspensions of Triademefon (0.1%), Wettable sulphur (0.3%), Dinocap (0.1%) and Myclobutanil (0.1%) at 15 days intervals, after disease appearance, controlled the disease effectively and increased seed yield. The maximum per cent disease control was recorded with spray of Triademefon upto 76.88 per cent. Wettable sulphur, Dinocap, Myclobutanil, Water spray inhibited the disease upto 74.50, 73.11, 67.66, 63.78 per cent, respectively. The significantly higher mean seed yield of 1435kg/ha was recorded with treatment Triademefon 0.1% followed by Wettable sulphur @ 0.3% (1330 kg/ha) and Dinocap @ 0.1% (1250 kg/ha). Similar trends were also recorded in case of test weight.